KLASTERING SUARA BERDASARKAN GENDER MENGGUNAKAN ALGORITMA K-MEANS DARI HASIL EKSTRAKSI FFT (Fast Fourier Transform) - Izzah, Nailul (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2018)
Speech recognition process is kind of applied  Technique of digital sign process that is widely used for many applications, for example technology in the field of telecommunications  which isn't  only able to provide for serving for sending text data but also it can serve for sending data using sound. From technology development of signal process emerges new idea to make application program by creating new sofware to display sound signal characteristic based on frequency and highest magnitude. Clustering is part of pattern recognition science which is made for system that can perform into a groups. In this research, the researcher will distinguish between male voice or female voice. Mechanism process uses Collecting  voice samples, then the feature extraction using  FFT  that  produce  two main  features  that is maximum  value of  frequency and maximun  value of  magnitude. After that, k-means alogarithm process is used  for grouping voice of  male clusteror  female cluster. The  result of this research uses 20 training data  and 20 testing data that will  produce 75% level of accuracy for training data and 100% for testing data.